Migration and social mobility within and between countries and its economic consequences in the period of globalization - Natig Shirinzade (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Ethnic and international conflicts have turned into a real headache for the modern world. The confrontations that have begun between the nations have escalated into serious conflicts that take the lives of thousands of innocent children, women and old people every year. Such conflicts create significant problems not only at the social level, but also at the political and economic level. If a decisive measure to resolve such conflicts has not been taken in a timely manner, the damage may prove irreparable. Our Institute of Global Economic Problems, represented by Natig Shirinzade, Ph.D. and Masters in Economics, Founder and Head of the Institute of Global Economic Problems decided to address this issue in greater detail and highlight the problem of the Nagorno-Karabakh conflict. Being citizens of the Republic of Azerbaijan, we are well acquainted with all the problems caused by interethnic conflicts and the subsequent flow of refugees and temporarily resettled. And therefore, we consider it our duty to cover such topics and bring them to the public court. This is one of the reasons for creating this organization - to provide people with reliable and verified information in order to help them overcome the difficulties of the Epoch of Globalization.
Keywords: F50; H56; J15; J17; J61; J62; J64; 330; Refugees; Ethnic conflicts; Labour market; Economic impact